(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Pharmacological interventions for diabetes predominantly involve chemically synthesized compounds, often causing undesirable side effects. This has led to a growing interest in plant-based therapeutic alternatives. Technological advancements have facilitated the discovery of bioactive phytochemicals with medicinal properties. This study employs molecular docking analysis to assess the anti-diabetic potential of a naturally derived compound, 4-[5-(Pyridin-4-yl)-1,2,4-oxadiazol-3-yl]-1,2,5-oxadiazol-3-amine (POA), obtained from Psidium guajava leaf extract. The evaluation focuses on its inhibitory action against four human proteins 11 β -HSD1 (PDB: 4K1L), GFAT (PDB ID: 2ZJ4), SIRT6 (PDB ID: 3K35) and Aldose reductase (PDB ID: 3G5E) associated with diabetes. Physicochemical, pharmacokinetic, and ADMET profiles were computed using online web servers Molinspiration, ADMETLAB 2.0, and SWISSADME. POA demonstrated superior binding affinity (in Kcal/mol) -8.0, -7.5, -8.9 and -9.5, respectively) compared to the widely used diabetic drug Metformin -5.4, -6.0, -5.4 and -7.2 with these receptor proteins. Based on molecular docking studies and pharmacokinetics/ADMET profiles, POA may act as a multi-targeted, less harmful, and more efficacious medication for Type 2 Diabetes Mellitus (T2DM) compared to Metformin.